Dietary emulsifiers from milk and soybean differently impact adiposity and inflammation in association with modulation of colonic goblet cells in high‐fat fed mice. Issue 3 (22nd December 2015) - Lecomte, Manon; Couëdelo, Leslie; Meugnier, Emmanuelle; Plaisancié, Pascale; Létisse, Marion; Benoit, Bérengère; Gabert, Laure; Penhoat, Armelle; Durand, Annie; Pineau, Gaëlle; Joffre, Florent; Géloën, Alain; et al.
Abstract : The effects of polar lipid emulsifier from milk (MPL) instead of soybean lecithin (SPL) were investigated in high‐fat fed mice. Compared with the control high‐fat diet devoid of polar lipids, high‐fat‐SPL diet increased white adipose tissue (WAT) mass, with larger adipocytes and increased expression of inflammation markers. This was not observed with high‐fat‐MPL diet, which induced instead a lower expression in WAT of macrophage infiltration markers and more goblet cells in the colon. This supports further exploration of different dietary emulsifiers in the frame of obesity outbreak. Abstract : Scope: Enhanced adiposity and metabolic inflammation are major features of obesity that could be impacted by dietary emulsifiers. We investigated in high‐fat fed mice the effects of using a new polar lipid (PL) emulsifier from milk (MPL) instead of soybean lecithin (soybean PL [SPL]) on adipose tissue and intestinal mucosa function. Methods and results: Four groups of C57BL6 mice received for 8 wks a low‐fat (LF) diet or a high‐fat diet devoid of PLs or an high‐fat diet including MPL (high‐fat‐MPL) or SPL (high‐fat‐SPL). Compared with high‐fat diet, high‐fat‐SPL diet increased white adipose tissue (WAT) mass ( p < 0.05), with larger adipocytes ( p < 0.05) and increased expression of tumor necrosis factor alpha, monochemoattractant protein‐1, LPS‐binding protein, and leptin ( p < 0.05). This was not observed with high‐fat‐MPL diet despite similar dietary intakes and increased expression of fatty acid transport protein 4 and microsomal TG transfer protein, involved in lipid absorption, in upper intestine ( p < 0.05). High‐fat‐MPL mice had a lower expression in WAT of cluster of differentiation 68, marker of macrophage infiltration, versus high‐fat and high‐fat‐SPL mice ( p < 0.05), and more goblet cells in the colon ( p < 0.05). Conclusions: Unlike SPL, MPL in the high‐fat diet did not induce WAT hypertrophy and inflammation but increased colonic goblet cells. This supports further clinical exploration of different sources of dietary emulsifiers in the frame of obesity outbreak.